MENAKAR PERAN PERGURUAN TINGGI DALAM PENGEMBANGAN INDUSRI BERKELANJUTAN - Putro, Moh. Zaenal Abidin Eko; Nurhayati, Ida (Parsimonia - Jurnal Ekonomi dan Bisnis, 2024)
The local community's ongoing agreement regarding plans to establish industries, as well as ongoing industries, certainly raises sociological and anthropological questions, namely what kind of relationship between the two, industry and society, has occurred so far. The most obvious case in this case can refer to the rejection of the people of Rempang Island, Batam City towards the plan to build Rempang Eco City, last September 2023. Seen from the perspective of the academic world, the problem of disharmony between the industrial world and local communities is important, apart from focusing on the relationship between the academic world and the industrial world. This paper with a desk research approach aims to describe the disharmonious relationship between the local community and the corporate community or the industrial world, looking for the root of the problem of rejection of investment and what offers universities can provide to the phenomenon of disharmony between the local community and the industrial world. The results of this research show that the implementation of a social permit to operate (SLO) is one of the agreements made to reconcile relations between local communities and investment and industry. In an effort to popularize SLO as a solution to the parameters of the relationship between the industrial world and local communities, the role of universities is very necessary.